Evaluation of Learners’ Satisfaction with Open Flexible and Distance Learning Services at the University of Lagos Distance Learning Institute - Oladipo, Adenike; Oladele, Esther O.; Ajeyalemi, Oladipupo; Afolabi, Folashade; Olayiwola, Peter O.; Adewara, Johnson A.; Akala, Andrew; Udeani, Uchenna (West African Journal of Open and Flexible Learning, 2024)
The prospects of Open and Distance Learning (ODL) as the best way to acquire formal education, especially having to work and learn simultaneously have led to curiosity in investigating the challenges that come with this great opportunity. This study evaluated learners’ satisfaction with the services provided by the Distance Learning Institute (DLI), University of Lagos, at various levels of learners’ engagement. A survey research design using non-probability quota sampling was adopted. Data was collected using a structured questionnaire which was developed and validated for testing learner satisfaction in ODL at the University of Lagos. A sample size of 3,724 learners was used for the study. Descriptive statistics such as frequencies, percentages, mean and standard deviation were used in analysing the data. Findings from this study revealed that DLI has been generally successful in satisfying learners at the pre-enrolment, process and product stages with mean response ratings of 7.27, 5.63, and 6.87 respectively. However, the learners were dissatisfied with the adequacy of course materials with a mean of 4.49 and radio lectures with a mean of 4.26. Furthermore, DLI graduates are slightly satisfied with the programme completion process such as result processing and convocation with mean response ratings of 7.74 and 7.44 but dissatisfied with the restrooms of mean 5.02. It is suggested that the administrators of DLI should adopt a continuous improvement approach, focusing on specific areas of the educational journey where satisfaction levels are low such as course materials, radio lectures, restrooms and related services to enhance graduate satisfaction. Résumé : La perspective de l’enseignement ouvert et à distance (EOD) comme meilleur moyen d’acquérir une éducation formelle, en particulier le fait de devoir travailler et apprendre simultanément, a suscité la curiosité d’enquêter sur les défis qui accompagnent cette grande opportunité. Cette étude a évalué la satisfaction des apprenants à l’égard des services fournis par le DLI de l’Université de Lagos, à différents niveaux d’engagement des apprenants. Un modèle de recherche par sondage utilisant un échantillonnage par quota non probabiliste a été adopté. Les données ont été collectées à l’aide d’un questionnaire structuré qui a été développé et validé pour tester la satisfaction des apprenants dans l’EOD à l’Université de Lagos. Un échantillon de 3 724 apprenants a été utilisé pour l’étude. Des statistiques descriptives telles que les fréquences, les pourcentages, la moyenne et l’écart-type ont été utilisées pour analyser les données. Les résultats de cette étude ont révélé que la DLI a moins de marge de progression pour satisfaire les apprenants aux stades de la préinscription, du processus et du produit, avec des réponses moyennes de 7,27, 5,63 et 6,87 respectivement. Les apprenants sont également insatisfaits de l’adéquation des supports de cours (moyenne de 4,49) et des conférences radiophoniques (moyenne de 4,26). En outre, les diplômés de DLI sont légèrement satisfaits du processus d’achèvement du programme tel que le traitement des résultats et la convocation avec des réponses moyennes de 7,74 et 7,44, mais insatisfaits des toilettes avec une moyenne de 5,02. Il est suggéré que les administrateurs de DLI adoptent une approche d’amélioration continue, en se concentrant sur des domaines spécifiques du parcours éducatif où les niveaux de satisfaction sont faibles, tels que le matériel de cours, les conférences radiophoniques, les toilettes et les services connexes, afin d’améliorer la satisfaction des diplômés. Mots-clés : Enseignement ouvert et à distance, services, satisfaction de l’apprenant